Differential binding of cyclic adenosine 3' ,5'-monophosphate to the cyclic adenosine 3' ,5'-monophosphate receptor protein in Escherichia coli. - Danley, D E (1977)
Binding of cyclic adenosine 3' ,5'-monophosphate (cAMP) by the cAMP receptor protein in crude cell-free extracts of Escherichia coli was characterized. When cell were grown in glucose, binding was inhibited 50% relative to extracts from cells grown with succinate as carbon source . This inhibition could be relieved by dialysis.